The Principal’s Attitude on Teacher Performance: A Case Study of Senior High School in South Tangerang Area - Nurdelima Waruwu; Fatkhul Arifin; Mufassirul Alam (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aimed to determine 1) to determine the effect of the principal's attitude on high school teachers’ performance in South Tangerang area, 2) to find out how much influence principal’s attitude has on teachers’ performances in South Tangerang, 3) to determine principal’s attitude that can affect teacher performance. This study employed a quantitative approach with correlational and ex post facto methods. The population was high school teachers in South Tangerang area while the subject of this study was 32 high school teachers in South Tangerang area. The independent variable (X) in this study is the principal’s attitude and the dependent variable (Y) in this study is teacher performance. Data collection techniques using a questionnaire and analysis method using Simple Regression. To test the hypothesis, correlation analysis and simple linear regression analysis were employed. Prior to the analysis test, the prerequisite tests were carried out, namely the normality test and the linearity test. Testing the hypothesis with a significance level of 5%, it was found that the p-value of the correlation between the principal's attitude variable and teacher performance was 0.079. The significance value of p > 0.05 (0.079 > 0.05). Because the value of F count is smaller than F table, it can be concluded that there is a significant influence between the variables of the principal's attitude on teacher performance.